Calidad de los conocimientos en el nivel inicial - Luna Pino, Pamela (2010)
The teaching-learning process is affected, primarily, at kindergarden due to many factors that marks the learning content quality, such as wrongly choosing the educationalmaterial. Most teachers deem that any object that attracts a child is an educational mean. However, in the end, this object may not serve as a learning facilitator, nor help to achieve theobjectives set out. The la e k of responsibility and professional ethics are shown by actions such as the lack planning of learning activities, as well as the lack of concern in giving the student a comprehensive education, thus drifting away from the purpose of teaching. The current use of traditional methodologies that are little conventional and limits children's potential development evidence the lack of continuous training and updating in new methodologies. The contextclosestto children's development or the children's individuality, interests, and personal needs are disregarded thus offering irrelevant activities to be developed, topics with contents that are of little interest for their comprehensive development, and also contents that are unnecessary for their independent performance throughout life. Finally, the lack of a didactic methodology to carry out activities is evidenced by leaving aside games, therefore overlooking its ludie, kinesthetic, and experimental principie that allows children to naturally learn with motivation and freedom, through their own body movements.